Journalism and literary theory: a combined perspective (Ogigia. Revista Electrónica de Estudios Hispánicos, 2019)
This article proposes a new approach to the study of journalistic texts. The theory of literature provides clues that reveal a very interesting fictional perspective built into the structure of the journalistic text. This study provides a methodology for the analysis of news articles which is based on their structure, but considers the appearance of items such as mimetic words, focalization, temporal usage, or the importance of the narrator as key motivations for the journalist, and offers a new perspective to the reader.
Keywords: News; Theory of literature; reader; journalism; fictionality